2022
DOI: 10.30574/wjaets.2022.7.1.0100
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of polyester composite reinforced hybrid Hibiscus tiliaceust bark and palm fibers as harrow comb (leveler) material

Abstract: In the present research preparation and characterization of polyester composite reinforced hybrid fiber Hibiscus tiliaceust bark fiber (HTBF) and palm fibers (PF). PF is obtained from palm plantation in Kekait village. HTBF has gained from the beach Krandangan, West Lombok, Indonesia. The fibers were treated with alkali by soaking it in 5% NaOH solution for 2 days Composites were made using the vacuum infusion method. The matrix used is polyester resin BTQN 157. The volume fractions between palm fibers (PF) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…It is also shown that the addition of the percentage of HTBF makes a significant contribution to the increase in the tensile strength of the specimen, where specimens without the addition of HTBF have lower tensile strength, for the three polyester composite specimens with 0 %, 5 % and 10 % CTBN filler. This is in accordance with the results of research from [11,12]. The change in tensile strain of the specimen polyester composite reinforced hybrid fiber MASF-HTBF with CTBN filler is shown in Fig.…”
Section: Tablesupporting
confidence: 91%
See 2 more Smart Citations
“…It is also shown that the addition of the percentage of HTBF makes a significant contribution to the increase in the tensile strength of the specimen, where specimens without the addition of HTBF have lower tensile strength, for the three polyester composite specimens with 0 %, 5 % and 10 % CTBN filler. This is in accordance with the results of research from [11,12]. The change in tensile strain of the specimen polyester composite reinforced hybrid fiber MASF-HTBF with CTBN filler is shown in Fig.…”
Section: Tablesupporting
confidence: 91%
“…3, a and Table 1. The tensile strength of the MASF-HTBF hybrid fiber reinforced polyester composite is higher than that of the MASF single fiber reinforced polyester composite, based on the results of [11]. The tensile strength of HTBF fiber is higher than that of MASF fiber, on the other hand the tensile strength of HTBF fiber is lower than that of MASF fiber.…”
Section: Discussion Of the Effect Hybrid Fiber And Filler Reinforcing...mentioning
confidence: 96%
See 1 more Smart Citation